2004
DOI: 10.17221/3683-pse
|View full text |Cite
|
Sign up to set email alerts
|

Study of European and Czech populations of potato cyst nematodes (Globodera rostochiensis and G. pallida) by RAPD method

Abstract: Potato cyst nematodes (PCN) are the big problem in worldwide planting of potatoes and another Solanaceous plants. Identification of individual pathotypes according to international scheme is very demanding but a very important part of the phytosanitary process to control these pests. Molecular genetic identification of different plant and animal species or individuals is a very interesting way at the present time and let's hope that it will be important in future. This report presents results of the RAPD study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…() reported that Phasmarhabditis hermaphrodita DNA was degraded in unpasteurized soil within 6 days; however, it should be noted that the P. hermaphrodita in the study was in the form of killed juveniles in direct contact with soil microflora, whereas the DNA of dead PCN is well‐protected by both the egg shells and the cyst wall. Other methods, such as protein isoelectric focusing (IEF; Ibrahim et al ., ), random amplification of polymorphic DNA (RAPD), random fragment length polymorphism (RFLP; Subbotin et al ., ; Sedlák et al ., ) and enzyme‐linked immunosorbent assays (ELISA; Fullaondo et al ., ; Ibrahim et al ., ), have also been used for the identification of PCN in the last 20 years. However, nowadays their impact is limited as a result of the establishment of PCR, a method which has proved to be more sensitive and accurate when compared with any of the above‐mentioned methods (Ibrahim et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…() reported that Phasmarhabditis hermaphrodita DNA was degraded in unpasteurized soil within 6 days; however, it should be noted that the P. hermaphrodita in the study was in the form of killed juveniles in direct contact with soil microflora, whereas the DNA of dead PCN is well‐protected by both the egg shells and the cyst wall. Other methods, such as protein isoelectric focusing (IEF; Ibrahim et al ., ), random amplification of polymorphic DNA (RAPD), random fragment length polymorphism (RFLP; Subbotin et al ., ; Sedlák et al ., ) and enzyme‐linked immunosorbent assays (ELISA; Fullaondo et al ., ; Ibrahim et al ., ), have also been used for the identification of PCN in the last 20 years. However, nowadays their impact is limited as a result of the establishment of PCR, a method which has proved to be more sensitive and accurate when compared with any of the above‐mentioned methods (Ibrahim et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex PCR and quantitative polymerase chain reaction (qPCR) are the two permitted probe-based detection methods of nematode species found in fish populations, such as Anisakis, Pseudo terranova, Hysterothylacium, and Contracaicum [45,46]. Multiplex PCR is efficiently applied in various biological and medical studies as it allows simultaneous amplification of many DNA fragments within one reaction [47].…”
Section: Probe-based Detection Methodsmentioning
confidence: 99%
“…Umarao et al (2002) used random operon primer OPG 5 to characterize the gene pool similarity of the field populations of PCN from Nilgiri Hills. Sedlak et al (2004) used RAPD analysis for studying genetic variability of nine different European and Czech populations of PCN. Typical RAPD profiles of individual populations were obtained by primers OPG 08 and OPG 13 (Table 3).…”
Section: Rapd-pcr (Random Amplified Polymorphic Dna-pcr) Based Characmentioning
confidence: 99%